Effect of Ion Mass and Charge State on Transport Vacuum Arc Plasmas Through a Biased Magnetic Filter - Eungsun Byon; Jong-Kuk Kim; Sik-Chol Kwon; André Anders (IEEE Transactions on Plasma Science, 2004)
The effect of ion mass and charge state on plasma transport through a 90 deg.-curved magnetic filter is experimentally investigated using a pulsed cathodic arc source. Graphite, copper, and tungsten were selected as test materials. The filter was a bent copper coil biased via the voltage drop across a low-ohm, selfbias resistor. Ion transport is accomplished via a guiding electric field, whose potential forms a trough shaped by the magnetic guiding field of the filter coil. Evaluation was done by measuring the filtered ion current and determination of the particle system coefficient, which can be defined as the ratio of filtered ion current, divided by the mean ion charge state, to the arc current. It was found that the ion current and particle system coefficient decreased as the mass-to-charge ratio of ions increased. This result can be qualitatively interpreted by a very simple model of ion transport that is based on compensation of the centrifugal force by the electric force associated with the guiding potential trough.
Keywords: Arc plasma; cathodic vacuum arc; ion charge states; macroparticle filter; plasma transport